Galling Damage to Woody Ornamentals: Diagnosis and Potential Causes - Adam Dale; Erin Harlow; Carrie Harmon; Chris Marble (EDIS)
Galling or witch’s broom damage on the newly expanding buds and leaves of woody ornamental plants has become increasingly common. Diagnosing this damage can be difficult because the most common causes are obscure or occur well before damage symptoms appear. This -page fact sheet written by and published by the UF/IFAS is intended to help landscape managers, nursery growers, and pest control professionals diagnose characteristic galling damage, mitigate damage that occurs, and, when possible, prevent it from occurring.